American Environmental History - Allosso, Dan (Open textbook library., 2019)
For too long the environment has been considered little more than a neutral background to history. This text surveys findings of the new field of Environmental History about how the environment of the Americas influenced the actions of people here and how people affected their environments, from prehistory to the present.